Kesetaraan Radikal: Analisis Pemikiran Pendidikan Jacques Ranciere - Ayi Hambali (Indonesian Journal of Sociology and Education Policy, 2017)
This article aimed to analyze the thought of Jacques Ranciere, especially those in the concentrated equity in education.A review of a new logic in the practice of emancipatory education of the new generation of French philosopher, Jacques Ranciere, which to this day is not too much known in discussions about education in Indonesia.Jacques Ranciere, known as an intellectual and a new generation of French philosophers.A critique of the explicative order he calls the myth of pedagogy that dominate the practice of educational practices today. Furthermore, the results of this study show that the conception of education Ranciere seeks to show ways to envision pedagogical practice as a form of intellectual emancipation, or in other words, a practice that verifies the equality of human intelligence. Realizedin practice through teaching methods introduced by Josep Jacotot with the name of Universal Teaching. To confirm the true nature of humanity that: â€œall men are equally intelligenceâ€.